WNT Signaling in Hematological Malignancies - Frenquelli, Michela; Tonon, Giovanni (Frontiers in Oncology, 2020)
The role of the WNT signalling pathway in key cellular processes, such as cell proliferation, differentiation and migration is well documented. WNT signalling cascade is initiated by the interaction of WNT ligands with receptors belonging to the Frizzled family, and/or the ROR1/ROR2 and RYK families. The downstream signalling cascade results in the activation of the canonical -catenin dependent pathway, ultimately leading to transcriptional control of cell proliferation, or the non-canonical pathway, mainly acting on cell migration and cell polarity. The high level of expression of both WNT ligands and WNT receptors in cancer cells and in the surrounding microenvironment suggests that WNT may represent a central conduit of interactions between tumor cells and microenviroment. In this review we will focus on WNT pathways deregulation in hematological cancers, both at the ligand and receptor levels. We will review available literature regarding both the classical -catenin dependent pathway as well as the non-canonical pathway, with particular emphasis on the possible exploitation of WNT aberrant activation as a therapeutic target, a notion supported by preclinical data.